Sosialisasi Digital Marketing Terhadap UMKM Promo Fostle Dan Babershop Do’a Ibu Di Kabupaten Sleman - Yohanes Dela Salle Batesa Leu; Hasim As’ari (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This article discusses the results and discussion of the digital marketing socialization program applied to MSME Promo Fostle and Barbershop Do'a Ibu in Sleman Regency. Results from the program include increased online presence, increased sales, and changes in the way these businesses utilize digital strategies. A discussion of implications and recommendations will also be discussed. The results achieved show that digital marketing has a significant positive impact on MSMEs. This success can be attributed to training, ongoing support and strong collaboration. Although MSMEs face challenges such as limited resources and adapting to change, these efforts provide valuable guidance for other MSMEs looking to utilize digital marketing. With a commitment to innovation and continued digital marketing practices, MSMEs can compete and develop in an increasingly digitally connected business world. The success of Promo Fostle and Barbershop Do'a Ibu MSMEs is an inspiring example for other MSMEs to pursue a similar journey towards more effective digital marketing and sustainable business growth